2005
DOI: 10.1177/0959-353505054715
|View full text |Cite
|
Sign up to set email alerts
|

‘Playing the Fool’: US Welfare Policy from a Critical Race Perspective

Abstract: In this article, we draw on critical race theory and critical race feminism to deconstruct contemporary US welfare policy. The political framing of work requirements, single motherhood, and ‘citizenship’ under the Personal Responsibility and Work Opportunity Reconciliation Act of 1996 are used to illustrate the racism, sexism, and classism that pervade current regulations. Drawing on Hurtado’s (1996) conceptuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Americans tend to perceive poverty and wealth status as an indication of personal attributes or worth (Cozzarelli, Wilkinson, & Tagler, 2001). Limbert and Bullock (2005) found that this contributes to the inequity of support for programs designed to benefit the poor and reduce inequalities such as the educational achievement gap. Finally, child development research has shown that parenting styles (Gutman & Eccles, 1999), exposure to cognitive stimulation (Bradley, Corwyn, McAdoo, & Garcia Coll, 2001), and the propensity to develop symptoms of psychopathology (Costello, Comptom, Keeler, & Angold, 2003) are all impacted by childhood poverty.…”
Section: Poverty Low Social Class and The School Counseling Relatiomentioning
confidence: 98%
“…Americans tend to perceive poverty and wealth status as an indication of personal attributes or worth (Cozzarelli, Wilkinson, & Tagler, 2001). Limbert and Bullock (2005) found that this contributes to the inequity of support for programs designed to benefit the poor and reduce inequalities such as the educational achievement gap. Finally, child development research has shown that parenting styles (Gutman & Eccles, 1999), exposure to cognitive stimulation (Bradley, Corwyn, McAdoo, & Garcia Coll, 2001), and the propensity to develop symptoms of psychopathology (Costello, Comptom, Keeler, & Angold, 2003) are all impacted by childhood poverty.…”
Section: Poverty Low Social Class and The School Counseling Relatiomentioning
confidence: 98%
“…Both CRT and CRF challenge the neutrality of child welfare policies and practices and show how these supposedly gender-neutral and raceneutral policies help to maintain the status quo. Child welfare workers, as state agents, are part of the power elite in the child welfare system and are thus implicated in maintaining the race, class, and gender hierarchies of oppression (Limbert & Bullock, 2005). Using the frameworks of CRT and CRF both honors the stories and counternarratives of Afro-Caribbean service users and simultaneously challenges structural and institutional oppression, including child welfare laws and policies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the fundamental tenets of CRT is storytelling, which is a critical tool that is well suited for study with Afro-Caribbean service users' and workers in the child welfare system. Both CRT and CRF challenge dominant majoritarian stories and broad power relations that uphold White power elites (Limbert & Bullock, 2005). They demand that we listen to and value the counter-stories and viewpoints of women and people of color on their intersecting oppressions (e.g., racism, classism, and sexism) and how these affect their lives (Limbert & Bullock, 2005;Razack & Jeffery, 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 97%
See 1 more Smart Citation
“…Here neo-liberalism infiltrates the construction of welfare mothers through their lack of both their own paid employment and the family support of a paid worker (Skevik, 2005). Within this account, welfare recipients are portrayed as irresponsible mothers who are poor because of their unrestrained sexuality, and have failed to meet the ideal of marriage and the nuclear family (Kingfisher, 1999;Limbert & Bullock, 2005;Rice, 2001). Provision of welfare is understood to undermine the family and present lone motherhood as a lifestyle choice for young women (Fineman, 1991;Uttley, 2000).…”
Section: Neo-liberalismmentioning
confidence: 97%